Disproportional Imprisonment of Black and Hispanic Males: Sentencing Discretion, Processing Outcomes, and Policy Structures - Ulmer, Jeffery; Painter-Davis, Noah; Tinik, Leigh (Justice quarterly, 2016)
Disproportional incarceration of black and Hispanic men has been the subject of much critical commentary and empirical inquiry. Such disproportionality may be due to greater involvement of minority men in serious crime, to discretionary decisions by local justice officials, or to the differential impact of sentencing policies, such as mandatory minimums or sentencing guidelines, that differentially impact minority men. This study investigated the extent to which the disproportional punishment of black and Hispanic men, and local variation in such disproportionality, can be attributed to unexplained disparities in local sentencing decisions, as opposed to the extent to which such differences are mediated by sentencing policies, or case-processing and extralegal factors. We use 2005-2009 federal court and Pennsylvania state court data. Our findings suggest, particularly in Federal courts, that most disproportionality is determined by processes prior to sentencing, especially sentencing policies that differentially impact minority males.